Low Price Guarantees in Markets with Low Search Costs - Harkins, Andrew (2007)
Offers by retailers to match or beat a competitor's lower price are ubiquitous in both consumer and industrial markets. The conventional understanding of these practices is that such firms are attempting to be as competitive as possible by selling at the lowest price in the market. Numerous game theoretic models have shown however that, on the contrary, low price guarantees may be anti-competitive devices which facilitate cartel pricing. Knowing that any attempts to undercut will be instantaneously matched, sellers have no incentive to compete on price. This research project is the first, to my knowledge, that empirically examines the role of low price guarantees in markets with low search costs.